Pedagogical Factors Influencing Training And Its Impact Towards Performance Among E-Commerce Entrepreneurs In Malaysia: Role Of Competencies As Moderator - Nasr, Noornasirah (2020)
Training is often seen as an effective tool to enable e-commerce entrepreneurs to create, develop, and enhance their knowledge or skills in creating good performance in terms of managing digital business. While many entrepreneurial training centres offer e-commerce programmes in Malaysia, however, the quality and usability of the training programmes are still a critical issue, where serious attention should be given. Hence, it is a vital need to study pedagogical factors that contribute to effective and relevant training in the segment of e-commerce entrepreneurs in Malaysia. This study is based on the Instructional Transaction Theory and Human Capital Theory. Thus, a holistic research model was built to study the pedagogical influence on training in the context of e-commerce entrepreneurs attending training at training centres offering ecommerce related programmes in Malaysia. This study also reviews the impact on the relationship between training and performance of entrepreneurs in operating their ecommerce business. Entrepreneur competency level is applied to understand the moderating effect between training and performance. Data were collected from 200 ecommerce entrepreneurs who attended training sessions in training centres offering ecommerce programmes in Malaysia through self-delivered surveys and online surveys involving five states: Selangor, Kuala Lumpur, Johor, Melaka, and Pulau Pinang. The collected data were analyzed using SPSS (Version 23) and SmartPLS (Versi 3.0) to test the proposed research hypotheses.